2016
DOI: 10.1002/jcph.840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Target‐Mediated Elimination on the Dose and Regimen of Evolocumab, a Human Monoclonal Antibody Against Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9)

Abstract: Understanding the pharmacokinetic (PK) and pharmacodynamic (PD) relationship of a therapeutic monoclonal antibody against proprotein convertase subtilisin/kexin type 9 (PCSK9) exhibiting target‐mediated drug disposition (TMDD) is critical for selecting optimal dosing regimens. We describe the PK/PD relationship of evolocumab using a mathematical model that captures evolocumab binding and removal of unbound PCSK9 as well as reduction in circulating low‐density lipoprotein cholesterol (LDL‐C). Data were pooled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 47 publications
8
50
0
1
Order By: Relevance
“…[38,53,76,156] An evolocumab study using a TMDD model showed that PCSK9 levels were higher in patients treated with statins. [38] This increase in PCSK9 levels may lead to higher target-mediated clearance of anti-PCSK9 mAbs.…”
Section: Influence Of Concomitant Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[38,53,76,156] An evolocumab study using a TMDD model showed that PCSK9 levels were higher in patients treated with statins. [38] This increase in PCSK9 levels may lead to higher target-mediated clearance of anti-PCSK9 mAbs.…”
Section: Influence Of Concomitant Treatmentmentioning
confidence: 99%
“…These predictions are achieved with the determination of TMDD parameters. [22] For some mAbs, TMDD models were used to estimate the dose needed to saturate mAb targetmediated elimination in most of patients, as for evolocumab [38] or obinutuzumab. [91] This approach may however lead to over-exposure of patients with low target antigen levels.…”
Section: Antigenic Targets Present In Several Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…4,10 In the assay, evolocumab was used for capture, and a second bioconjugated anti-PCSK9 antibody was used for detection to ensure PCSK9 bound to evolocumab was not measured. 4,10 In the assay, evolocumab was used for capture, and a second bioconjugated anti-PCSK9 antibody was used for detection to ensure PCSK9 bound to evolocumab was not measured.…”
Section: Methodsmentioning
confidence: 99%
“…4 Current US Food and Drug Administration recommendations offer minimal guidance on the disposition of therapeutic proteins in patients with RI. The available clinical evidence supports a lack of effect of mild or moderate RI on the clearance of evolocumab, which is similar to the clearance of other large monoclonal antibodies.…”
mentioning
confidence: 99%